2020
DOI: 10.35333/jrp.2020.221
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico assessment of antiproliferative activity of new acetamides bearing 1,3,4-oxadiazole and pyrimidine cores via COX inhibition

Abstract: Lung cancer is not only the most commonly diagnosed cancer type but also the leading cause of cancer related deaths throughout the world. The advanced methods for lung cancer therapy have focused on the development of new targeted agents. Cyclooxygenase (COX) is one of the most crucial targets for lung cancer therapy. In the current work, new compounds (1-12) containing 1,3,4-oxadiazole and pyrimidine cores within the acetamide framework were synthesized and evaluated for their cytotoxic effects on A549 human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…The IC50 values ( Table 6 ) obtained from cell survival plots ( Figures S3–S6 ) showed that the SBA–15–RuSalen compound has the most potent antitumor efficiency, with a concentration of 23.9 μg/mL being able to inhibit half of A549 cells’ growth compared to control after 72 h. The selectivity index (the ratio between the IC 50 for normal cell line and IC 50 for the cancer cell line) for this compound was 2.4, proving the higher toxicity against tumor cells than against normal ones. By comparing the result of SBA–15–RuSalen with a positive control, such as cisplatin, the standard therapy for patients with lung cancer [ 53 ], we observed an almost-similar IC 50 value (26 ± 3.0 μg/mL), as it was previously reported [ 54 ] after 72 h of incubation of this drug with A549 cells. Furthermore, it is important to highlight that all Ru-containing hybrid materials exhibited lower IC 50 values compared to the SBA–15 compound.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The IC50 values ( Table 6 ) obtained from cell survival plots ( Figures S3–S6 ) showed that the SBA–15–RuSalen compound has the most potent antitumor efficiency, with a concentration of 23.9 μg/mL being able to inhibit half of A549 cells’ growth compared to control after 72 h. The selectivity index (the ratio between the IC 50 for normal cell line and IC 50 for the cancer cell line) for this compound was 2.4, proving the higher toxicity against tumor cells than against normal ones. By comparing the result of SBA–15–RuSalen with a positive control, such as cisplatin, the standard therapy for patients with lung cancer [ 53 ], we observed an almost-similar IC 50 value (26 ± 3.0 μg/mL), as it was previously reported [ 54 ] after 72 h of incubation of this drug with A549 cells. Furthermore, it is important to highlight that all Ru-containing hybrid materials exhibited lower IC 50 values compared to the SBA–15 compound.…”
Section: Resultssupporting
confidence: 79%
“…The IC50 values (Table 6) obtained from cell survival plots (Figures S3-S6) showed that the SBA-15-RuSalen compound has the most potent antitumor efficiency, with a concentration of 23.9 μg/mL being able to inhibit half of A549 cells' growth compared to control after 72 h. The selectivity index (the ratio between the IC50 for normal cell line and IC50 for the cancer cell line) for this compound was 2.4, proving the higher toxicity against The IC50 values (Table 6) obtained from cell survival plots (Figures S3-S6) showed that the SBA-15-RuSalen compound has the most potent antitumor efficiency, with a concentration of 23.9 µg/mL being able to inhibit half of A549 cells' growth compared to control after 72 h. The selectivity index (the ratio between the IC 50 for normal cell line and IC 50 for the cancer cell line) for this compound was 2.4, proving the higher toxicity against tumor cells than against normal ones. By comparing the result of SBA-15-RuSalen with a positive control, such as cisplatin, the standard therapy for patients with lung cancer [53], we observed an almost-similar IC 50 value (26 ± 3.0 µg/mL), as it was previously reported [54] after 72 h of incubation of this drug with A549 cells. Furthermore, it is important to highlight that all Ru-containing hybrid materials exhibited lower IC 50 values compared to the SBA-15 compound.…”
Section: Cytotoxicity Evaluationsupporting
confidence: 78%
“…Based on these unique features, 1,3,4-oxadiazole-carrying compounds exhibit a broad biological activity spectrum, including anticancer effects. Zibotentan, with a 1,3,4-oxadiazole core, is an important anticancer agent and a lead compound for developing new 1,3,4-oxadiazole-based anticancer agents [46][47][48][49]. In a study performed by El-Sayed et al [50], novel heterocyclic oxadiazoles were synthesized and evaluated for their anticancer effects as dual selective COX-2 and EGFR inhibitors.…”
Section: Introductionmentioning
confidence: 99%